The presentation of a model of an electronic patient record system for use in general practice in South Africa - De Wet, Lizette (University of the Free State, 1999)
Information drives the practice of medicine. Unfortunately physicians drown in the amount of information engulfing their day-to-day tasks. The invention of the patient record was the first step in trying to bring order to this situation. Numerous problems are, however, experienced worldwide with the manual paper patient records that have been in use in medical practices for the past few years. The obvious answer to overcome these problems is an electronic patient record (EPR). In South Africa (SA) the EPR is not generally used, despite its well-known potential advantages. Focusing on general practice, a research project therefore was undertaken to: • Ascertain whether a need for EPR systems exists • Identify problems associated with current paper medical records • Identify the requirements, expectations, and needs regarding EPR systems • Design and present prototype EPR systems for evaluation and testing by general practitioners (GPs) in SA according to their requirements, expectations, and needs as mentioned above • Present the GPs of SA with a model of a proposed EPR system, specifically designed for their requirements, expectations, and needs. The results of questionnaires that were sent out indicated that the GPs in SA realised the need for implementing computers in their practices. As in many parts of the world, they do experience frustrating problems with their current manual systems. These include misfiled and lost files, difficulty in recording external work, the identification of old, unused files, the durability and transferability of files, duplication, illegible/incomprehensible files that become too thick too fast, and the physical storage space for these files. The computer systems currently used in general practice focus mainly on administrative and financial duties, and there is a need to integrate these functions with clinical EPR's. The GPs also gave an indication of the type of system they would consider implementing. Abstract 529 Despite some problems that were foreseen, a clear impression was left that GPs believed in the concept of the EPR, that they definitely felt a need for it and that they would use it (personally), when available. Two prototype EPR systems were developed. The first prototype was demonstrated to a group of GPs to get a general idea of the system's compliance with their requirements. It was further put to the test by applying heuristic and usability evaluation methods. The latter was done in conjunction with the paper and pencil observation technique. The results of these evaluation methods were analysed and applied in the development of the second prototype. After the completion of the second prototype EPR system, a third alternative, namely the HUB Medical Computer System (based on the Foresighted Practice Guidelines principle) was acquired. It was deemed important to test this as an alternative to the template principle on which the first two prototypes were based. The second prototype and HUB were evaluated in a hands-on laboratory evaluation. Similar evaluations techniques to those applied to the first prototype were performed on the second prototype as well. Additionally the first and second prototypes were compared to each other with the aid of a task analysis. The users identified positive aspects in the HUB system. The second prototype was, however, received with enthusiasm. By taking the evaluation results to heart and using the second prototype as basis, an EPR model was thus presented. Broadly viewed, this model involves a graphical user interface (accessed via mouse/keyboard) based on the Tab-method, entering of consultations via the SOAP model, a query, report and printing facility, customization, and communication with the health care environment via e-mail and medical protocols. In future EPR systems for GPs in SA could be based on this model.

Inligting is die dryfveer vir mediese praktykvoering. Ongelukkig verdrink geneeshere in die hoeveelheid inligting wat hulle dag-vir-dag take verswelg. Die uitvinding van die pasiëntrekord was die eerste stap in die poging om die situasie te probeer orden. Verskeie probleme word egter wêreldwyd met die papier (hand) pasiëntrekordstelsels, wat vir die afgelope paar jaar in gebruik is in mediese praktyke, ondervind. Die logiese oplossing om dié probleme te probeer oorkom, is 'n elektroniese pasiëntrekord (EPR). Ten spyte van sy alombekende voordele, word die EPR nog nie algemeen in Suid-Afrika (SA) gebruik nie. Met die oog op die algemene praktyk, is 'n navorsingsprojek dus onderneem om: • Te bepaal of'n behoefte aan 'n EPR bestaan • Probleme wat met huidige papier mediese rekords bestaan, te identifiseer • Die vereistes, verwagtings en behoeftes rakende die EPR the identifiseer • EPR prototipe-stelsels te ontwerp en aan algemene praktisyns (AP's) in SA voor te lê vir evaluasie en toetsing na aanleiding van hulle vereistes, verwagtings en behoeftes • 'n Model van 'n voorgestelde EPR stelsel, spesifiek ontwerp vir hulle vereistes, verwagtings en behoeftes, aan AP's in SA voor te lê. Die resultate van vraelyste wat uitgestuur is dui aan dat AP's in SA die behoefte aan die implementering van rekenaars in hulle praktyke besef. Net soos in verskeie dele van die wêreld ondervind hulle frustrerende probleme met hulle huidige handstelseis. Dit sluit in foutief-geliasseerde en verlore lêers, probleme in die vaslegging van eksterne werk, die identifikasie van ou, ongebruikte lêers, die duursaamheid en oordraagbaarheid van lêers, duplikasie, onleesbare/onverstaanbare lêers wat te vinnig te dik word en die tekort aan fisiese stoorspasie vir die lêers. Die rekenaaarstelsels wat tans in algemene praktyk gebruik word fokus meestalop administratiewe en finansiële take en daar is 'n behoefte aan die integrasie van hierdie funksies met die kliniese EPR. Die AP's het ook aangedui watter tipe stelsel hulle vir implementering sal oorweeg. Ten spyte van probleme wat voorsien word, is 'n duidelike indruk gelaat dat die AP's in die EPR-konsep glo, dat hulle beslis 'n behoefte daaraan het en dat hulle dit (persoonlik) sal gebruik, indien beskikbaar. Twee prototipe EPR stelsels is ontwikkel. Die eerste prototipe is aan 'n groep AP's gedemonstreer om 'n algehele gevoel te kry van die stelsel se voldoening aan hulle vereistes. Dit is verder getoets deur heuristiese- en bruikbaarheids-evaluasiemetodes toe te pas. Laasgenoemde is uitgevoer aan die hand van die papier-en-pen observasietegniek. Die resultate van hierdie evaluasiemetodes is ontleed en toegepas in die ontwikkeling van die tweede prototipe. Na voltooiing van die tweede EPR prototipe is 'n derde alternatief, naamlik die "HUB Medical Computer System" (gebaseer op die sogenaamde "Foresighted Practice Guidelines" beginsel), aangeskaf Die toets hiervan as alternatieftot die templaat beginsel waarop die eerste twee prototipes geskoei is, is as belangrik beskou. Die tweede prototipe en die HUB is in 'n "hands-on" laboratorium-situasie ge-evalueer. Soortgelyke evaluasietegnieke as dié wat op die eerste prototipe uitgevoer is, is ook op die tweede prototipe uitgevoer. Die eerste en tweede prototipes is addisioneel met mekaar vergelyk aan die hand van 'n taakanalise. Die gebruikers het positiewe aspekte in die HUB geïdentifiseer. Die tweede prototipe is egter met entoesiasme ontvang. Deur die evaluasieresultate ter harte te neem en die tweede prototipe as basis te gebruik, is 'n EPR model voorgestel. Basies behels die model 'n grafiese gebruikerkoppelvlak (met toegang via die muis/sleutelbord), gebaseer op die Tab-metode, die invoer van konsultasies via die SOAP model, 'n navraag-, verslag- en drukfasiliteit, gebruikeraanpassings en kommunikasie met die gesondheidsorgomgewing via e-pos en mediese protokolle. In die toekoms kan EPR stelsels vir AP's In SA op hierdie model gebaseer word.
Thesis (Ph.D. (Computer Science and Informatics))--University of the Free State, 1999
Keywords: Electronic patient record; EPR; Computerized patient record; CPR; PMR; EPR model; Computer-based patient record; General practice; Paper medical record; Medical records -- Data processing; Medical informatics